Bipolar Disorder after COVID-19 Infection: A Case Report from an Ethiopian Perspective - Elias Tesfaye; Selamawit Alemayehu; Elias Gebru (Case Reports in Psychiatry)
Introduction. COVID-19 has been a sudden public health crisis since January 2020, spreading from the city of Wuhan, China, to the whole country within a month and posing serious threats to lives. The pandemic has a profound effect on all aspects of society, including mental health and physical health. The actual effect of the virus on the brain and possible psychiatric manifestations is still an area of study and further investigation. There are also several case reports showing manic like symptoms after COVID-19 infection. We describe the case of a 55-year-old patient who presented with behavioral and mood symptoms after a COVID-19 infection. Case Presentation. The patient presented with behavioral disturbance after a diagnosis of COVID-19. He exhibited symptoms including irritability, verbal and physical aggressiveness, increased goal-directed activity, elated and expansive mood, increased energy, grandiosity and inflated self-esteem, and decreased need for sleep. Findings on psychiatric evaluation encompassing detailed history and mental state examination suggested bipolar disorder due to COVID-19 infections. For this, he was put on sodium valproate 1000 mg per day and later, and he was discharged after 21 days with improvement. Conclusions. This case highlights the importance of paying attention to psychiatric symptoms in patients with COVID-19 and the early intervention and involvement of psychiatrists especially in critically ill patients. In the present scenario, we urge physicians to pay attention to those cases and be open-minded for such a possible new diagnosis. We also recommend performing antibody tests for CSF and RNA tests for patients with mental abnormalities following COVID-19. Further studies can be performed to identify the relationship between COVID-19 and bipolar disorders.